Against IP-adjunction scrambling - Yamada, Makoto (Kansas Working Papers in Linguistics, 1997)
As an optional movement, "scrambling" in Japanese has been one of the major obstacles to the Minimalist program, in which movements occur only when necessary. Miyagawa (1996), in his attempt to accommodate this phenomena to the MP, argues that VPadjunction scrambling should be analyzed as base-generated constructions and suggests that IP-adjunction scrambling is motivated by some special element like Focus. This paper argues that if we make a natural extension of the categories which can assume strong features, the IP-adjunction scrambling phenomena. too, can be accounted for in the MP without stipulating any special element. Ibis study implies that except that a lexical category V can bear a strong D-feature. nothing is special about Japanese phrase structure.